Meta-analysis of Virtual-based Chromoendoscopy Compared With Dye-spraying Chromoendoscopy Standard and High-definition White Light Endoscopy in Patients With Inflammatory Bowel Disease at Increased Risk of Colon Cancer. Issue 9 (8th February 2020) - El-Dallal, Mohammed; Chen, Ye; Lin, Qianyun; Rakowsky, Shana; Sattler, Lindsey; Foromera, Joshua; Grossberg, Laurie; Cheifetz, Adam S; Feuerstein, Joseph D
Abstract : The yield of virtual chromoendoscopy to enhance colorectal cancer detection in IBD is unclear. In this meta-analysis of 11 randomized control trials, virtual chromoendoscopy was not different from dye-based chromoendoscopy or high definition white light endoscopy with biopsies in detecting patients with at least one colon lesion, however, virtual chromoendoscopy was inferior to high definition white light endoscopy in detecting number of lesions. Abstract: Background: Patients with inflammatory bowel disease (IBD) have an increased risk of colorectal cancer. We sought to assess the comparative efficacy of virtual chromoendoscopy (VCE) vs high definition white light endoscopy (HDWLE) or dye-spraying chromoendoscopy (DCE) through a meta-analysis and rating the quality of evidence. Methods: A systematic review of the literature was performed through February 15, 2019. Primary outcomes were number of patients in whom dysplasia was identified and number of dysplastic lesions identified in these patients. We included only randomized control trials (RCTs) and performed meta-analysis using RevMan5.3. Results: Of the 3205 studies identified, 11 RCTs were included, with a total of 1328 patients. Per patient analysis, VCE was not statistically different compared with DCE (risk ratio [RR] 0.77; 95% CI, 0.55–1.08) or HDWLE (RR 0.72; 95% CI, 0.45–1.15). However, per dysplasia analysis, VCE was not statistically different compared with DCE (RR 0.72; 95% CI, 0.47–1.11) and inferior compared with HDWLE (RR 0.62; 95% CI, 0.44–0.88). The quality of evidence was moderate in the HDWLE and low to moderate in the DCE studies. Conclusion: Based on this meta-analysis, VCE was as good as HDWLE and DCE in identifying dysplasia per patient analysis. However, per dysplasia analysis, VCE was inferior compared with HDWLE and no different from DCE. Further studies need to examine the efficacy of each individual VCE technique.